2013
DOI: 10.1063/1.4790586
|View full text |Cite
|
Sign up to set email alerts
|

Potential energy curves for the interaction of Ag($\mathbf {5}{\bm s}$5s) and Ag($\mathbf {5}{\bm p}$5p) with noble gas atoms

Abstract: We investigate the interaction of ground and excited states of a silver atom with noble gases (NG), including helium. Born-Oppenheimer potential energy curves are calculated with quantum chemistry methods and spin-orbit effects in the excited states are included by assuming a spin-orbit splitting independent of the internuclear distance. We compare our results with experimentally available spectroscopic data, as well as with previous calculations. Because of strong spin-orbit interactions, excited Ag-NG potent… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 48 publications
(110 reference statements)
1
9
0
Order By: Relevance
“…The correlation contribution of the outer-core electrons to the interaction energy was found to be less than 0.4% in the case of NH 3 -Ar 33 and it is thus neglected in the present study, even though the effect is expected to increase for the heavier rare gases Kr and Xe. 44 The value of the T1 diagnostic [45][46][47] was inferior to 0.01 for all geometries and all rare gas species, which demonstrates the single-reference character of the wave function.…”
Section: A Ab Initio Calculationsmentioning
confidence: 99%
“…The correlation contribution of the outer-core electrons to the interaction energy was found to be less than 0.4% in the case of NH 3 -Ar 33 and it is thus neglected in the present study, even though the effect is expected to increase for the heavier rare gases Kr and Xe. 44 The value of the T1 diagnostic [45][46][47] was inferior to 0.01 for all geometries and all rare gas species, which demonstrates the single-reference character of the wave function.…”
Section: A Ab Initio Calculationsmentioning
confidence: 99%
“…Core-valence interactions can indeed alter the interaction energy significantly for heavy noble gases. 44 Twenty-six electrons were correlated in these calculations, which become prohibitively expensive with large basis sets. As can be seen from the last column of Table I, the effect is rather small (less than 0.4%) and can be neglected.…”
mentioning
confidence: 99%
“…All states of interest correlate with ground state Ar atoms plus low-lying 4d 10 5s ( 2 S), 4d 10 5p ( 2 P) and 4d 9 5s 2 ( 2 D) terms of Ag. Qualitatively similar curves exist for the other Ag-RG complexes [15] although Loreau et al recently showed that the excited state potentials show marked deviation from Morse functions when spin-orbit coupling is included. The A states of Ag-He and Ag-Ne are particularly anomalous supporting double well structures.…”
Section: Introductionmentioning
confidence: 56%
“…[14] The same states have recently been the subject of a detailed computational study at the spin-unrestricted coupled cluster level (UCCSD(T)) by Loreau et al. [15] A different excited state labelling is employed by Loreau et al but we have adopted labels consistent with Brock and Duncan. All states of interest correlate with ground state Ar atoms plus low-lying 4d 10 5s ( 2 S), 4d 10 5p ( 2 P) and 4d 9 5s 2 ( 2 D) terms of Ag.…”
Section: Introductionmentioning
confidence: 99%